A dual gate material tunnel field effect transistor model incorporating two‐dimensional Poisson and Schrodinger wave equations. (11th July 2021) - Mohanty, Sadhana Subhadarshini; Dutta, Pradipta; Das, Jitendra Kumar
Abstract: This paper presents an accurate analytical model of surface potential and drain current for a long channel dual material gate (DMG) tunneling field‐effect transistor (TFET) with the addition of nonlinear inversion charge developed at the channel/drain interface region, ambipolar characteristic, and quantum confinement. The model includes the effect of dual metal gate work function as it controls the threshold voltage without considering a fully depleted undoped channel region. The current model includes the effect of charge accumulation at the interface of two gates and an appropriate mathematical expression of nonlinear inversion charge developed at the interface of two gates has been derived from the two‐dimensional (2D) Schrodinger wave equation incorporating quantum confinement. The model is effective to capture transfer characteristics at Sub 10 nm body thickness. A high I ON / I OFF ratio and less than 27 mV/decade subthreshold swing are achieved at 2 nm body thickness which is desirable for low power VLSI application. The proposed model has been compared and calculated by Sentaurus TCAD with fair accuracy and a good resemblance, including ambipolar characteristics at sub 10 nm body thickness has been achieved.